The Effect of Chitosan and Polyvinyl Alcohol Combination on Physical Characteristics and Mechanical Properties of Chitosan-PVA-Aloe vera Film - Dioni fadia Zatalini; Esti Hendradi; Philip Drake; Retno Sari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Wound is a condition where there is damage or disruption to the anatomical structure and function of the skin. Wounds that are not treated properly can lead to infection. As wound dressings, film dressings have many advantages such as being elastic, flexible, transparent, and can adapt to the wound shape. Film's characteristics of are affected by the plasticizer and the polymer. Combination of chitosan and polyvinyl alcohol (PVA)  is able to improve the mechanical properties of the film such as its swelling capacity, tensile strength, and elongation at break. Objective: This study aims to determine the effects of chitosan and PVA in various concentrations on the physical characteristics and mechanical properties of the film. Methods: Film was prepared by solvent casting method, using chitosan and alginate in various concentrations of 0% to 1.5%, 1.5% Aloe vera, and 6% propylene glycol. Films' characteristics and mechanical properties were evaluated, such as swelling index, tensile strength, elongation at break, and Young's modulus. Results: The result showed that chitosan and PVA polymers had a significant effect on the swelling index, tensile strength, elongation at break, and Young's modulus. The effect of chitosan and PVA combination on the swelling index, tensile strength, and elongation at break is due to the hydrogen bonding between the hydroxyl group of PVA and the amine group of chitosan. Conclusion: The combination of chitosan and polyvinyl alcohol influenced the film's physical and mechanical properties. Film with chitosan and polyvinyl alcohol ratio of 1.5%:1.5% have best characteristics compared to others.